Tailoring technologies to the rehabilitational needs of stroke survivors - Rennick-Egglestone, Stefan (2014)
Stroke is a major cause of physical disability. Recovery is possible, and can continue indefinitely. As such, much of it will take place at home, often with minimal support from professional therapists. As computing becomes more pervasive and familiar, opportunities exist to design technology to support rehabilitation in the home environment. However, given the varied nature of disabilities caused by stroke, there is a need for a greater understanding of how to design technology that is sufficiently tailored to the needs of individuals and which is appropriate for usage in their homes. This thesis offers an exploration of these issues, through a series of research activities constructed around the direct participation of stroke survivors and their families.